Analisis Relevansi Isi Buku Teks Bahasa Indonesia Kawan Seiring Kelas III terhadap Capaian Pembelajaran Fase B Tahun 2025 - Bambang Bambang; Anwar Anwar; Adhy Putri Rilianti; Ahmad Rif'an Najih (STKIP AL HIKMAH SURABAYA, 2026)
The revision of the 2025 Phase B Indonesian Language Learning Outcomes has created a need to re-evaluate the relevance of textbooks currently used in the implementation of the Merdeka Curriculum. This study aims to analyze the content relevance of the Kawan Seiring Grade III Indonesian language textbook to the 2025 Phase B Learning Outcomes. A qualitative evaluative approach employing deductive content analysis was adopted. The data sources consisted of the Kawan Seiring Student Book, Teacher's Guide, and the Decree of the Head of the Agency for Standards, Curriculum, and Educational Assessment No. 046/H/KR/2025. All eight chapters were analyzed based on the four Learning Outcomes elements: listening, reading and viewing, speaking and presenting, and writing. The findings indicate that all Learning Outcomes elements are represented in the textbook, although with varying degrees of coverage. The strongest alignment was found in reading and viewing, speaking and presenting, and writing, while listening activities remain largely dependent on teacher narration and are not consistently supported by standardized audio resources. The textbook also demonstrates coherence among learning objectives, learning activities, assessments, and multimodal texts, although improvements are needed in structured presentation tasks, independent writing activities, and digital learning resources. Overall, the findings suggest that Kawan Seiring remains relevant as a primary learning resource for the early stage of Phase B, provided that teachers adapt its implementation to learners' needs and current curriculum requirements.